A prospective study of weight and height going from infancy to adolescence - Tienboon P. (2014)
Weight and height from infancy to age 15 years was studied in the Geelong population (n = 1200 in infancy; n = 213 at adolescence), Victoria, Australia. Body mass index (BMI) increased from 3 months to 12 months and then decreased again until 80 months after which it increased to 20.5 kg/m2 at the age of 15 years. The extent of tracking of BMI in infants classified as overweight or underweight was similar and differed from that of subjects of normal weight. Only one in four of the infants classified as overweight or underweight in infancy were still in the same category in adolescence, compared with three in four of those classified as of normal weight. Socioeconomic status has an effect on weight and height status in adolescence but not on the tracking of BMI. The age at 6-7 years is a critical age for weight and height status in adolescence. It appears that weight and height in infancy have a significant relationship with body size in adolescence but only in boys.